SLC26A9-mediated chloride secretion prevents mucus obstruction in airway inflammation - Anagnostopoulou, Pinelopi; Dürr, Julia; Agrawal, Raman; Schatterny, Jolanthe; Mall, Marcus A. (The journal of clinical investigation, 2012)
Asthma is a chronic condition with unknown pathogenesis, and recent evidence suggests that enhanced airway epithelial chloride (Cl-) secretion plays a role in the disease. However, the molecular mechanism underlying Cl- secretion and its relevance in asthma pathophysiology remain unknown. To determine the role of the solute carrier family 26, member 9 (SLC26A9) Cl- channel in asthma, we induced Th2-mediated inflammation via IL-13 treatment in wild-type and Slc26a9-deficient mice and compared the effects on airway ion transport, morphology, and mucus content. We found that IL-13 treatment increased Cl- secretion in the airways of wild-type but not Slc26a9-deficient mice. While IL-13-induced mucus overproduction was similar in both strains, treated Slc26a9-deficient mice exhibited airway mucus obstruction, which did not occur in wild-type controls. In a study involving healthy children and asthmatics, a polymorphism in the 3' UTR of SLC26A9 that reduced protein expression in vitro was associated with asthma. Our data demonstrate that the SLC26A9 Cl- channel is activated in airway inflammation and suggest that SLC26A9-mediated Cl- secretion is essential for preventing airway obstruction in allergic airway disease. These results indicate that SLC26A9 may serve as a therapeutic target for airway diseases associated with mucus plugging.